2004
DOI: 10.1111/j.1395-3907.2004.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Colour blindness in everyday life and car driving

Abstract: ABSTRACT.Purpose: The aim of the present work was to ascertain, through the administration of a psychosocial questionnaire, the difficulties that subjects with defective colour vision experience in carrying out everyday tasks and work, including driving a car with a driver's licence held for no more than 3 years. Methods: Subjects with defective colour vision (n = 151) and subjects with normal vision (n = 302) completed a psychosocial questionnaire regarding the difficulties associated with congenital colour v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 19 publications
(37 reference statements)
0
46
0
2
Order By: Relevance
“…On the contrary, Tagarelli et al showed there were no differences between the two groups in identifying the colours of traffic light signals. However, when the relative positions of the traffic lights were changed, more CVD subjects had difficulty identifying the colours than NCV subjects but the difference was not statistically significant [22].…”
Section: Driving and Accidentsmentioning
confidence: 82%
See 4 more Smart Citations
“…On the contrary, Tagarelli et al showed there were no differences between the two groups in identifying the colours of traffic light signals. However, when the relative positions of the traffic lights were changed, more CVD subjects had difficulty identifying the colours than NCV subjects but the difference was not statistically significant [22].…”
Section: Driving and Accidentsmentioning
confidence: 82%
“…Furthermore, the highest educational qualification was not significantly associated with colour vision status [21]. Another 2004 questionnaire survey showed no significant difference in the disciplines studied between NCV and CVD persons, but CVD interviewees tended towards technical studies (30%, as opposed to 18% of NCV subjects), and less of them undertook tertiary education in university (68.9%, as opposed to 79.9% of NCV subjects) [22].…”
Section: School Agementioning
confidence: 93%
See 3 more Smart Citations